SISTEM INFORMASI PELAPORAN HASIL PRESTASI BELAJAR SANTRI TPQ PP. SHIROTUL FUQOHAâ II KALIPARE â MALANG - Farida, Eni; Afifuddin, Ahmad (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2012)
Computer-based information systems have been widely applied in various fields of life including the education sector in terms of delivering accurate, relevant and timely, so as to produce quality information.Similarly, PP TPQ. Shirotul Fuqoha II that the development requires a system of information reporting the results of a web-based learning students that aims to display some information, especially about the daily value based on the achievements of students, in addition to the information received to be more rapid, accurate on time so that the learning outcomes of students pesetas learning activities can be monitored easily and accurately. Web-based information system is built using the programming language PHP with MySQL as the database and Mozilla Firefox as a browser. Keywords: Information Systems, The Learning Achievement, PP TPQ. Shirotul Fuqoha II